The Effect of The formal and Organizational Properties on the Aesthetic Evaluation ofthe ArChiteCtural Design Project :’AccOrding lo the specialw ofthe lraqi Academic Experience’1 - Jasim, Nagham Ahmed (Iraqi Journal of Architecture and Planning, 2018)